The establishment and formation of the Scientific Society named after Shevchenko as an important factor in consolidating Ukrainians - Medvid, F. M. (History of science and technology, 2016)
The article reveals the emergence of a number of natural and human societies in the Ukrainian lands. Of particular importance for the development of science and culture of Ukraine was the Shevchenko Society, which united in its ranks scientists of the natural and humanitarian sphere, who launched a series of Ukrainian Studies. The author analyzes the formation of the Shevchenko Scientific Society, reveals Ukrainian centered nature of the three sections of the Society and contribution of its scientists in the Ukrainian and world science.